Monitoring and Evalution Strategies in Education Units - Ari Anggara; Faisal Rahman; Faridah Faridah; Muhammad Faraiddin; Maria Desi Siregar; Nila Syafrida (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2022)
Along with the times and increasing needs to make business processes more complex, including in the field of education. Indicators of school success in carrying out its program are seen from the suitability of the process with what is planned, suitability in achieving goals, effective and efficient use and utilization of resources, as well as the ability to provide guarantees for the suitability of processes and achievement of goals through a control mechanism that is harmonious and fully embedded in system. Monitoring and evaluation aims to obtain information used for decision making. The results of monitoring will be used to provide guidance in the form of input (feedback), for improving program implementation, while the results of the evaluation can provide information that can be used to provide input for all components.